Efeito sinérgico da suplementação oral com L-glutamina e da natação de moderada intensidade na modulação da resposta imune na asma experimental - Oliveira, Vinícius José de (2024)
Introduction: Non-pharmacological treatments for asthma control play a significant role in improving the quality of life for patients, complementing the conventional drug-based approach. Interventions such as disease education and regular physical exercise have demonstrated positive impacts on asthma management. Aim: Evaluate the effects promoted by oral supplementation with the amino acid L-glutamine and moderate-intensity swimming, either individually or combined, on the immunological and morphofunctional parameters of an experimental model of asthma. Materials and Methods: 120 female BALB/c mice, weighing approximately 20 grams and aged between 5 and 8 weeks, were sensitized twice with 50 μg of ovalbumin (OVA) grade V (i.p.) at 7-day intervals. Sequentially, during the challenge phase, the animals received instillations of 20 μL of a suspension containing 10 μg of OVA grade V for five days. As a treatment, the animals underwent moderate-intensity swimming five times a week for four weeks and received oral supplementation of L-glutamine at doses of 1 g/kg of the animal's weight during the same periods as swimming. Parameters evaluated included tidal volume, respiratory rate, minute volume, physical conditioning, specific IgE and IgG antibody levels to OVA, IgG subclasses (IgG1 and IgG2a), cytokines, plasma lactate, and lung histopathology. Statistical analysis was performed using Graph Pad Prism 6. Results: After following a swimming and supplementation program for four weeks, mice showed improved physical conditioning, reduced release of plasma lactate, recovery of baseline respiratory parameters, decreased levels of Th2 profile cytokines (IL-5), increased regulatory cytokines (IL-10), and Th1 profile cytokines (IFN-γ). Additionally, histological restoration in the lungs was observed. However, among the analyzed groups, no significant variations were recorded in the humoral immune response of asthmatic animals subjected to the therapies used. Conclusion: Swimming and L-glutamine supplementation demonstrated a significant impact on the anti-inflammatory effect of experimental asthma. It was identified that the applied therapies modulated immune responses associated with asthma. The combination of these two approaches showed synergistic effects, reducing bronchial inflammation in experimental asthma.